Pengaruh Persepsi Manfaat, Persepsi Kemudahan Penggunaan, dan Brand Image Terhadap Niat Penggunaan Bank Digital Seabank: Studi pada Generasi Z di Kecamatan Buleleng - Kadek Dena Ade Mahamerta; Komang Endrawan Sumadi Putra (Journal of Innovative and Creativity, 2026)
The rapid growth of digital banking services in Indonesia has not been fully accompanied by optimal user adoption, particularly among Generation Z, who still express concerns regarding security and trust. This study aimed to examine the effect of perceived usefulness, perceived ease of use, and brand image on the intention to use SeaBank digital banking services among Generation Z in Buleleng District. A causal quantitative approach was employed, and data were collected through questionnaires distributed to 150 respondents selected using purposive sampling. The collected data were analyzed using multiple linear regression with statistical software assistance. The results show that perceived usefulness, perceived ease of use, and brand image simultaneously have a significant effect on the intention to use SeaBank. Partially, perceived usefulness and perceived ease of use have a positive and significant effect, while brand image has a negative and significant effect on intention to use. These findings indicate that functional benefits and ease of use are the main drivers of intention, whereas SeaBank’s brand image has not yet fully strengthened user confidence.